2018
DOI: 10.1136/openhrt-2018-000910
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery among patients with heart failure: a systematic review and meta-analysis

Abstract: BackgroundBariatric surgery reduces cardiovascular risk in obese patients. Heart failure (HF) is associated with an increased perioperative risk following bariatric surgery. This systematic review aimed to assemble the evidence on bariatric surgery in patients with known HF and the potential effect of bariatric surgery on incident HF in obese patients without prevalent HF.MethodsWe performed a comprehensive literature search up to 30 September 2017 and included studies comparing bariatric surgery to non-surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Consistent with the reduction in incident hypertension in the present study, bariatric surgery was also associated with a significant reduction in the risk of HF compared with the control group. A systematic review summarizing the impact of bariatric surgery using data from seven studies found a reduction in incident HF in patients who had bariatric surgery, similar to the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the reduction in incident hypertension in the present study, bariatric surgery was also associated with a significant reduction in the risk of HF compared with the control group. A systematic review summarizing the impact of bariatric surgery using data from seven studies found a reduction in incident HF in patients who had bariatric surgery, similar to the present study.…”
Section: Discussionsupporting
confidence: 83%
“…During our data analysis, we performed a routine indexation to BSA, and we found that BSA indexation introduced a paradoxical increase in LA and LV dimensions after surgery. We think that this finding is of no clinical significance, considering the clinical observations of reduced incidence of atrial fibrillation and heart failure after surgically induced weight loss [20][21][22][23][24]. We believe that these findings reflect well-known difficulties in cardiac chamber indexation in severe obesity [48].…”
Section: Limitationsmentioning
confidence: 77%
“…Data from the literature suggests that the risk of atrial arrhythmia and HFpEF is increased in obesity and with the presence of LA mechanical dysfunction measured by strain. On the other hand, the increased risk of AF and HFpEF in obesity is effectively reduced by surgically induced weight loss [20][21][22][23][24].…”
Section: Key Pointsmentioning
confidence: 99%
“…There are no RCTs evaluating cardiovascular outcomes between metabolic surgery and conventional treatment for obesity. However, data suggest that the incidence of heart failure is lower after metabolic surgery 88 . Propensity‐matched cohort studies have found a risk reduction of incident heart failure by 62% and a 50% lower risk in all‐cause mortality in hospitalized patients with heart failure in patients with prior metabolic surgery 78,89 .…”
Section: Efficacy Of Metabolic Surgerymentioning
confidence: 99%